How to raise and market ostriches - Parkolwa, M. (Acacia Stantex Publishers / CTA / Friends-of-the-Book Foundation, 2003)
This book is aimed at farmers planning to raise ostriches on a commercial basis. Among the topics covered are breeding practices, diseases affecting ostriches, feed management and the overall commercial environment, including guidance on the process of marketing ostriches effectively.